Strategi Guru Dalam Menangani Cyberbullying Pada Generasi Alpha Melalui Pembelajaran Pendidikan Agama Islam Studi Kasus di MI Bahrul Ulum - Muassisatul Fatihah (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2025)
Generation Alpha will be the most tech-savvy generation in history.┬á From playing, learning, to socializing through various online channels. As Generation Alpha's dependence on technology increases, so does their vulnerability to emerging online risks, such as cyberbullying. This research aims to identify and analyze the strategies applied by teachers in dealing with cyberbullying in the Alpha generation through Islamic Religious Education learning at MI Bahrul Ulum. This research uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews with teachers, observation, and document analysis related to the education program implemented. The results showed that teachers at MI Bahrul Ulum implemented several strategies, such as providing education about akhlakul karimah, the digitalization era and the dangers of cyberbullying, and inviting students to get used to doing religious activities such as reading the Qur'an and praying dhuha in congregation before starting learning in class, then in between PAI lessons the teacher will explain the dangers of cyberbullying and the importance of maintaining oral and akhlakul karimah, as well as holding activities related to cyberbullying.Keywords: Teacher Strategy, Cyberbullying, PAI Learning┬á